Business ethics contemporary issues and cases - Spinello, Richard A. 1950- (SAGE, 2020)
The future of the free market depends on fair, honest business practices. Business Ethics: Contemporary Issues and Cases aims to deepen students' knowledge of ethical principles, corporate social responsibility, and decision-making in all aspects of business. The text presents an innovative approach to ethical reasoning grounded in moral philosophy. Focusing on corporate purpose-creating economic value, complying with laws and regulations, and observing ethical standards-a decision-making framework is presented based upon Duties-Rights-Justice. Over 40 real-world case studies allow students to grapple with a wide range of moral issues related to personal integrity, corporate values, and global capitalism. Richard A. Spinello delves into the most pressing issues confronting businesses today including sexual harassment in the workplace, cybersecurity, privacy, and environmental justice Give your students the SAGE edge! SAGE edge offers a robust online environment featuring an impressive array of free tools and resources for review, study, and further exploration, keeping both instructors and students. Learn more at edge.sagepub.com/spinello.